Answer:
hi i will help you with this
Step-by-step explanation:
Step-by-step explanation:
8k -2z = 16
to solve for k let's add 2z both sides
8k = 16+2z
divide both sides of the equation by 8
8k/8= 16+2z/8
k= 16+2Z /8
Factor to this equation out, the easiest way is to solve for the two x values that add up to -1 but when multiplied is equal to -6. It should look like this: (x +- ?)(x +- ?).
The factored out form is then (x - 3)(x +2), because -3 + 2 = -1 and when multiplied together gives -6.
x - 3 = 0
x = 3
x + 2 = 0
x = -2
The two solutions are therefore, x = 3 and x = -2.
Hope it helps
Answer:
Step-by-step explanation:
I think you meant x^(3/2). This breaks down in at least two ways:
[x^3]^(1/2), or √(x^3)m or √x³), or
[x^(1/2)]^3 = (√x)^3
53×2=106
2×53=106
106×1=106
1×106=106